Analytical Study of Cognitive Emotion Regulation on Parental Psychological Control and Adolescent Suicidal Behavior - Song, Yiren (Transactions on Social Science, Education and Humanities Research, 2023)
Purpose: To explore the effects of parental psychological control on adolescent suicidal self-injurious behavior and the mediating role of negative cognitive emotion regulation strategies. METHODS: The Parental Psychological Control Scale, the Cognitive Emotion Regulation Questionnaire, and the Adolescent Self-Injurious Behavior Questionnaire were administered to 583 middle school students. Results: (1) Parental psychological control, negative cognitive emotion regulation strategies, and suicidal behavior were positively correlated; (2) Negative cognitive emotion regulation strategies mediated parental psychological control and suicidal behavior; and (3) Negative cognitive emotion regulation strategies mediated parental psychological control and suicidal self-injurious behavior.